SYSTEMATIC LITERATURE REVIEW: PENGARUH GOOD CORPORATE GOVERNANCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - Steviane Valentina; Trinandari Prasetya Nugrahanti (Bajang Institute, 2025)
Financial reporting quality is a key indicator of organizational accountability and transparency in supporting stakeholders’ decision-making. Improvements in financial reporting quality are increasingly influenced by the effectiveness of Good Corporate Governance (GCG) and the adoption of technology-based accounting information systems. This study aims to synthesize the role of GCG, particularly internal control and audit committees, as well as accounting information systems based on Enterprise Resource Planning (ERP) and Artificial Intelligence (AI) in enhancing financial reporting quality. A Systematic Literature Review (SLR) was conducted on 22 national and international journal articles. The findings indicate that GCG positively affects financial reporting quality through stronger oversight mechanisms, while ERP and AI improve accuracy, timeliness, and transparency of financial reporting. However, technological implementation requires robust governance and data security to mitigate emerging risks.